A low linear expansion coefficient polyphenylene sulfide composite material, a preparation method and application thereof

By introducing a combination of sheet-like, fibrous, and nano-sized fillers into PPS materials and combining them with specific processes, a polyphenylene sulfide composite material with a low linear expansion coefficient was prepared. This solved the problem of PPS material expansion under temperature changes and improved the dimensional stability and mechanical properties of the material.

CN122628546APending Publication Date: 2026-08-25SHANDONG MINGQUAN SPECIAL NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611004513.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-08-25

AI Technical Summary

Technical Problem

Existing PPS materials have a high coefficient of linear expansion under temperature changes, which affects the assembly accuracy and service stability of products. Existing modification schemes are difficult to balance low expansion performance with comprehensive mechanical properties.

Method used

A low-linear-expansion-coefficient polyphenylene sulfide composite material was prepared by using a low-expansion filler system, including sheet-like, fibrous, and nano-sized fillers, combined with high-speed premixing and twin-screw extrusion processes.

Benefits of technology

It significantly reduces the linear expansion coefficient of the material, improves dimensional stability, and maintains high tensile strength, flexural strength and impact performance, making it suitable for high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application belongs to the technical field of polymer composites, and discloses a low linear expansion coefficient polyphenylene sulfide composite material, a preparation method and application thereof. The composite material comprises 20-60 parts of polyphenylene sulfide resin, 40-80 parts of a low expansion filler system, 0.5-5 parts of a coupling agent, 0.1-1 part of a lubricant and 0.1-1 part of a toning agent. The low expansion filler system is at least two of a lamellar structure filler, a fibrous structure filler and a nano-sized filler. The polyphenylene sulfide composite material obtained has a low linear expansion coefficient while maintaining good mechanical properties through the limiting effect of the lamellar structure filler on the thermal expansion of the resin matrix, the reinforcing effect of the fibrous structure filler on the strength and modulus of the material and the improvement effect of the nano-sized filler on the filling structure and the interface state. The polyphenylene sulfide composite material can be applied to the fields of precision instruments, electronic packaging, electronics and electrical appliances, automobiles and aerospace, etc. which have high requirements for thermal dimensional stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field, specifically relating to a low linear expansion coefficient polyphenylene sulfide composite material, its preparation method, and its application. Background Technology

[0002] Polyphenylene sulfide (PPS) is a semi-crystalline thermoplastic engineering plastic with good heat resistance, chemical corrosion resistance, high mechanical properties, good flame retardancy, and good dimensional stability. It is widely used in electronics, automotive, aerospace, and precision structural components.

[0003] With increasing demands for dimensional stability in electronic packaging, precision instruments, automotive precision components, and high-temperature structural components, the linear expansion of PPS materials under temperature variations has gradually become a significant factor limiting their further application. Traditional PPS materials have a high coefficient of linear expansion, making them prone to dimensional changes in high-temperature or alternating hot and cold environments, which in turn affects the assembly accuracy, sealing reliability, and long-term service stability of products.

[0004] In existing technologies, to reduce the linear expansion coefficient of PPS, modifications such as inorganic filler filling, fiber reinforcement, or polymer blending are commonly used. Flaky inorganic fillers are beneficial for reducing the linear expansion coefficient, but when added in high amounts, the toughness and strength of the material may decrease. Fiber-reinforced materials can improve the strength and modulus of the material, but when used alone, they still have insufficient control over thermal expansion in different directions. Nanoscale fillers can improve filler gaps and interfacial conditions, but when added alone in small amounts, they are difficult to significantly reduce the overall linear expansion coefficient of PPS composites.

[0005] Therefore, existing PPS modification schemes still have the problem of not being able to balance low expansion performance and comprehensive mechanical properties. Especially in application scenarios that require low linear expansion coefficient, high modulus, high strength and good processing stability at the same time, a PPS composite material technology solution with reasonable formulation structure and strong process feasibility is still needed. Summary of the Invention

[0006] The purpose of this invention is to provide a polyphenylene sulfide composite material with a low linear expansion coefficient and its preparation method, so as to solve the problems of insufficient thermal dimensional stability of existing PPS materials and the difficulty of a single filler system in achieving both low linear expansion coefficient and comprehensive mechanical properties.

[0007] To achieve the above objectives, the present invention adopts the following technical solution.

[0008] On one hand, the present invention provides a polyphenylene sulfide composite material with a low linear expansion coefficient, comprising the following components by weight: 20-60 parts of polyphenylene sulfide resin, 40-80 parts of a low expansion filler system, 0.5-5 parts of coupling agent, 0.1-1 parts of lubricant, and 0.1-1 parts of colorant.

[0009] Preferably, the weight-average molecular weight of the polyphenylene sulfide resin is 20,000 to 30,000.

[0010] Preferably, the low-expansion packing system comprises at least two of the following: sheet-like packing, fibrous packing, and nano-sized packing.

[0011] Preferably, the sheet-like filler is one or more of talc, mica, and graphene.

[0012] More preferably, the aspect ratio of the sheet-like packing is greater than 30.

[0013] The sheet-like filler can form a layered confinement structure in the PPS matrix, reducing the dimensional change tendency of the resin matrix after heating, and is especially beneficial to reducing the linear expansion coefficient of the material in the flow direction.

[0014] Preferably, the fibrous filler is one or more of ultrafine glass fiber, carbon fiber or basalt fiber.

[0015] More preferably, the fibrous packing has a length of 6-13 mm and a diameter of 1-10 μm.

[0016] Fibrous fillers can form a reinforcing skeleton in the PPS matrix, improving the tensile strength, flexural strength and tensile modulus of the material, thereby compensating for the possible decrease in mechanical properties caused by highly filled sheet fillers.

[0017] Preferably, the nano-sized filler is one or more of silicon micropowder, carbon nanotubes, and glass microspheres.

[0018] More preferably, the particle size of the nano-sized filler is 10~300nm.

[0019] Nanoscale fillers can fill the tiny gaps between sheet-like and fibrous fillers and the PPS matrix, improving the packing state and interfacial bonding of the composite filler system, thereby enhancing the overall performance of the material.

[0020] Preferably, the low-expansion packing system includes sheet-like packing, fibrous packing, and nano-sized packing.

[0021] More preferably, the low-expansion packing system includes 20-40 parts of sheet-like packing, 10-20 parts of fibrous packing, and 10-20 parts of nano-sized packing.

[0022] In a further preferred embodiment, the sheet-like filler is talc powder, and the fibrous filler is ultrafine glass fiber.

[0023] Preferably, the coupling agent is one or more of silane coupling agents and titanate coupling agents.

[0024] Preferably, the silane coupling agent includes one or more of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0025] Preferably, the titanate coupling agent includes one or more of isopropoxytriisostearoyl titanate, isopropoxytris(dioctylphosphoyloxy)titanate, and di(dioctylpyrophosphoyloxy)oxyacetic acid titanate.

[0026] Preferably, the lubricant is at least one of a polysiloxane compound and an ester wax.

[0027] Preferably, the polysiloxane compound includes silicone masterbatch and / or silicone powder. The silicone masterbatch includes at least one of KMP~590, KMP~591, and KJ~A01; the silicone powder includes at least one of X~52~1620 and ST~LS100.

[0028] Preferably, the colorant is high-temperature resistant carbon black.

[0029] Secondly, the present invention provides a method for preparing the above-mentioned low linear expansion coefficient polyphenylene sulfide composite material, comprising the following steps: S1. Weigh out the polyphenylene sulfide resin, low-expansion filler system, coupling agent, lubricant and colorant by weight. S2. Add the polyphenylene sulfide resin and coupling agent to a high-speed mixer and mix them to pre-disperse the coupling agent on the surface of the PPS resin. S3. Add lubricant and colorant to the mixture obtained in step S2 and continue mixing; when the formula contains nano-sized fillers, add the nano-sized fillers together with the lubricant and colorant and mix. S4. Add the mixture obtained in step S3 into a twin-screw extruder, while separately feeding the sheet-like filler and / or fibrous filler. After melt blending, extrusion, cooling, and pelletizing, a polyphenylene sulfide composite material with a low linear expansion coefficient is obtained.

[0030] Preferably, the mixing time in step S2 is 2 minutes.

[0031] Preferably, the mixing time in step S3 is 2 minutes.

[0032] Preferably, in step S4, the temperatures of each zone of the twin-screw extruder from the feed inlet to the die are set sequentially as follows: 250℃, 250℃, 325℃, 325℃, 325℃, 325℃, 315℃, 315℃, 315℃, 315℃, 330℃.

[0033] Preferably, in step S4, the feed rate of the twin-screw extruder is 30 kg / h and the screw speed is 300 rpm.

[0034] Preferably, the twin-screw extruder in step S4 is A 35mm×2 twin-screw extruder with a length-to-diameter ratio (L / D) of 44.

[0035] Thirdly, the present invention also provides the application of the above-mentioned low linear expansion coefficient polyphenylene sulfide composite material in precision instruments, electronic packaging, electronic and electrical components, automotive components or aerospace components.

[0036] Compared with the prior art, the present invention has at least the following beneficial effects: 1. This invention introduces a low-expansion filler system into PPS resin, resulting in a material with a significantly lower linear expansion coefficient than unmodified PPS material, thereby improving the dimensional stability of the material under temperature change conditions.

[0037] 2. This invention combines sheet-like and fibrous fillers, allowing the low expansion effect of the sheet-like filler and the reinforcing effect of the fibrous filler to complement each other, thus maintaining high tensile strength, flexural strength, tensile modulus, and impact performance while reducing the linear expansion coefficient.

[0038] 3. In the embodiment where nano-sized fillers are further added, the nano-sized fillers can improve the dispersion and interstitial state of the filler system in the PPS matrix, thereby improving the overall performance stability of the material.

[0039] 4. The present invention adopts a preparation process that combines high-speed premixing with twin-screw extrusion. The process flow is simple, the equipment is highly versatile, and it is suitable for industrial continuous production. Detailed Implementation

[0040] To enable those skilled in the art to better understand the present application, the technical solutions in specific embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by those skilled in the art.

[0041] Unless otherwise stated, all "parts" in this instruction manual refer to parts by weight.

[0042] Example 1 This embodiment provides a polyphenylene sulfide composite material with a low linear expansion coefficient, comprising the following components by weight: 28.1 parts polyphenylene sulfide resin, 35 parts talc, 35 parts ultrafine glass fiber, 0.8 parts coupling agent KH550, 0.5 parts silicone masterbatch, and 0.6 parts carbon black.

[0043] The preparation method is as follows: Polyphenylene sulfide resin and coupling agent KH550 were added to a high-speed mixer and mixed for 2 minutes. Then, silicone masterbatch and carbon black were added sequentially and mixed for another 2 minutes. Talc powder and ultrafine glass fiber were fed separately and co-extruded and granulated using a twin-screw extruder.

[0044] The temperatures of each zone from the feed inlet to the die head of the twin-screw extruder are set sequentially as follows: 250℃, 250℃, 325℃, 325℃, 325℃, 325℃, 315℃, 315℃, 315℃, 315℃, 330℃.

[0045] The feed rate is 30 kg / h, and the screw speed is 300 rpm. The specifications of the twin-screw extruder are as follows: 35mm×2, L / D=44.

[0046] In this embodiment, talc powder is used as a sheet-like filler to reduce the thermal expansion of the PPS matrix, and ultrafine glass fiber is used as a fibrous filler to improve the strength and modulus of the material. The combination of the two enables the material to achieve a good balance between low expansion performance and mechanical properties.

[0047] Example 2 This embodiment provides a polyphenylene sulfide composite material with a low linear expansion coefficient, comprising the following components by weight: 28.1 parts polyphenylene sulfide resin, 67 parts talc, 3 parts nanostructure filler, 0.8 parts coupling agent KH550, 0.5 parts silicone masterbatch, and 0.6 parts carbon black.

[0048] The nanostructure filler is spherical silica powder.

[0049] The preparation method is as follows: Polyphenylene sulfide resin and coupling agent KH550 were added to a high-speed mixer and mixed for 2 minutes. Then, silicone masterbatch, spherical silica powder, and carbon black were added sequentially and mixed for another 2 minutes. Talc powder was fed separately and co-extruded and granulated using a twin-screw extruder.

[0050] The temperature, feed rate, screw speed, and equipment specifications of the twin-screw extruder are the same as in Example 1.

[0051] In this embodiment, a higher content of talc can effectively reduce the linear expansion coefficient of the material, and spherical silica powder is used as a nanostructure filler to improve the packing state of the filling system.

[0052] Example 3 This embodiment provides a polyphenylene sulfide composite material with a low linear expansion coefficient, comprising the following components by weight: The composition includes 28.1 parts polyphenylene sulfide resin, 35 parts talc, 32 parts ultrafine glass fiber, 3 parts nanostructure filler, 0.8 parts silane coupling agent, 0.5 parts silicone masterbatch, and 0.6 parts carbon black.

[0053] The nanostructure filler is spherical silica powder.

[0054] The preparation method is as follows: Polyphenylene sulfide resin and silane coupling agent were added to a high-speed mixer and mixed for 2 minutes. Then, silicone masterbatch, spherical silica powder, and carbon black were added sequentially and mixed for another 2 minutes. Talc powder and ultrafine glass fiber were fed separately and co-extruded and granulated using a twin-screw extruder.

[0055] The temperature, feed rate, screw speed, and equipment specifications of the twin-screw extruder are the same as in Example 1.

[0056] In this embodiment, talc, ultrafine glass fiber, and spherical silica powder together constitute a low-expansion filler system. Talc is used to limit the thermal expansion of the PPS matrix, ultrafine glass fiber is used to form a reinforcing skeleton, and spherical silica powder is used to improve the filler gaps and interface conditions, enabling the material to achieve better overall performance.

[0057] Comparative Example 1 This comparative example provides a polyphenylene sulfide composite material, which, by weight, comprises the following components: 28.1 parts polyphenylene sulfide resin, 70 parts talc, 0.8 parts coupling agent KH550, 0.5 parts silicone masterbatch, and 0.6 parts carbon black.

[0058] The preparation method is as follows: Polyphenylene sulfide resin and coupling agent KH550 were added to a high-speed mixer and mixed for 2 minutes. Then, silicone masterbatch and carbon black were added sequentially and mixed for another 2 minutes. Talc powder was fed separately via side feeding and co-extruded and granulated using a twin-screw extruder.

[0059] The temperature, feed rate, screw speed, and equipment specifications of the twin-screw extruder are the same as in Example 1.

[0060] Comparative Example 2 This comparative example provides a polyphenylene sulfide composite material, which, by weight, comprises the following components: 63.1 parts polyphenylene sulfide resin, 35 parts talc, 0.8 parts coupling agent KH550, 0.5 parts silicone masterbatch, and 0.6 parts carbon black.

[0061] Except for the different formulation, the preparation process is the same as that of Comparative Example 1.

[0062] Comparative Example 3 This comparative example provides a polyphenylene sulfide composite material, which, by weight, comprises the following components: The composition includes 63.1 parts polyphenylene sulfide resin, 35 parts ultrafine glass fiber, 0.8 parts coupling agent KH550, 0.5 parts silicone masterbatch, and 0.6 parts carbon black.

[0063] Except for the different formulation, the preparation process is the same as that of Comparative Example 1.

[0064] Comparative Example 4 This comparative example provides a polyphenylene sulfide composite material, which, by weight, comprises the following components: 95.1 parts of polyphenylene sulfide resin, 3 parts of nanostructured filler, 0.8 parts of coupling agent KH550, 0.5 parts of silicone masterbatch, and 0.6 parts of carbon black.

[0065] The nanostructured filler is spherical silica powder.

[0066] Except for the different formulation, the preparation process is the same as that of Comparative Example 1.

[0067] Comparative Example 5 This comparative example provides a polyphenylene sulfide composite material, which, by weight, comprises the following components: The composition includes 63.1 parts polyphenylene sulfide resin, 35 parts ordinary glass fiber, 0.8 parts coupling agent KH550, 0.5 parts silicone masterbatch, and 0.6 parts carbon black.

[0068] Except for the different formulation, the preparation process is the same as that of Comparative Example 1.

[0069] Test case This test example performs performance tests on the materials obtained in Examples 1-3 and Comparative Examples 1-5, as well as the blank control (polyphenylene sulfide resin). The test items and methods are as follows: The tensile properties were tested according to ISO 527-1 / -2; the flexural strength was tested according to ISO 178; the impact strength of the simply supported beam was tested according to ISO 179 / 1eU; and the linear expansion coefficient was tested according to ISO 11359-1 / -2. The test results are shown in the table below.

[0070] Table 1: Mechanical Performance Test Results

[0071] Table 2: Test results of linear expansion coefficient

[0072] As shown in Tables 1 and 2, the linear expansion coefficient of the blank sample in the flow direction at room temperature is 6.6 × 10⁻⁶. -5 / ℃, the linear expansion coefficient in the flow direction at 200℃ is 10.9×10. -5 / ℃. The linear expansion coefficient of the polyphenylene sulfide composite materials obtained in Examples 1-3 in the flow direction at room temperature is 1.6 × 10⁻⁶. -5 The temperature was significantly lower than that of the blank sample, indicating that the low-expansion filler system of the present invention can effectively reduce the linear expansion coefficient of PPS material.

[0073] Example 1 uses a combination of talc and ultrafine glass fiber. The material has a tensile strength of 120 MPa, a tensile modulus of 18 GPa, a flexural strength of 220 MPa, and a notched impact strength of 6 kJ·m for a simply supported beam. -2 The linear expansion coefficient in the flow direction at room temperature is 1.6 × 10⁻⁶. -5 / ℃. This result indicates that the combined use of sheet-like and fibrous packing materials can reduce the coefficient of linear expansion while maintaining good mechanical properties.

[0074] Example 3 uses a combination of talc, ultrafine glass fiber, and spherical silica powder. The material has a tensile strength of 124 MPa, a tensile modulus of 21 GPa, a flexural strength of 236 MPa, and a notched impact strength of 7.2 kJ·m for a simply supported beam. -2 The linear expansion coefficient in the flow direction at room temperature is 1.6 × 10⁻⁶. -5 At 200℃, the linear expansion coefficient in the flow direction is 2.1×10⁻⁶. -5 / ℃. This result indicates that adding nanostructured fillers to the base of sheet-like and fibrous fillers is beneficial for further improving the overall performance of the material.

[0075] Comparative Example 1 and Example 2 both exhibited low coefficients of linear expansion, but their mechanical properties were relatively low, indicating that while simply relying on a high content of sheet-like filler can reduce the coefficient of linear expansion, it is difficult to balance strength and toughness. Comparative Example 4, with only a small amount of nanostructured filler added, had a coefficient of linear expansion of 6.5 × 10⁻⁶ in the flow direction at room temperature. -5 The temperature was close to that of the blank sample, indicating that a small amount of nanostructured filler alone is insufficient to effectively reduce the linear expansion coefficient of PPS materials. Comparative Examples 3 and 5 show that the fiber-reinforced system can improve mechanical properties, but the overall control effect on the linear expansion coefficient is still not as good as the implementation method combining sheet-like and fibrous fillers.

[0076] Therefore, through the combined design of the low-expansion filler system, this invention enables PPS composite materials to have a low linear expansion coefficient under both room temperature and high temperature conditions, while maintaining good mechanical properties, making them suitable for application scenarios with high requirements for thermal dimensional stability and structural performance.

[0077] Finally, it should be noted that the described embodiments are merely some, not all, of the embodiments of the present invention. Those skilled in the art will understand that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the claims and their equivalents; that is, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A polyphenylene sulfide composite material with a low linear expansion coefficient, characterized in that, By weight, it comprises the following components: 20-60 parts of polyphenylene sulfide resin, 40-80 parts of low-expansion filler system, 0.5-5 parts of coupling agent, 0.1-1 parts of lubricant, and 0.1-1 parts of colorant, wherein the low-expansion filler system is at least two of the following: sheet-like filler, fibrous filler, and nano-sized filler.

2. The composite material according to claim 1, characterized in that, The low-expansion packing system includes 20-40 parts of sheet-like packing, 10-20 parts of fibrous packing, and 10-20 parts of nano-sized packing.

3. The composite material according to claim 1, characterized in that, The aspect ratio of the sheet-like filler is greater than 30, and the sheet-like filler is one or more of talc, mica, and graphene.

4. The composite material according to claim 1, characterized in that, The length of the fibrous structure filler is 6~13mm and the diameter is 1~10μm. The fibrous structure filler is one or more of ultrafine glass fiber, carbon fiber or basalt fiber.

5. The composite material according to claim 1, characterized in that, The particle size of the nano-sized filler is 10~300nm, and the nano-sized filler is one or more of silicon micropowder, carbon nanotubes, and glass microspheres.

6. The composite material according to claim 1, characterized in that, The coupling agent is one or more of silane coupling agents and titanate coupling agents. Among them, the silane coupling agent includes one or more of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and the titanate coupling agent includes one or more of isopropoxytriisostearoyl titanate, isopropoxytris(dioctylphosphoyloxy)titanate, and di(dioctylpyrophosphoyloxy)oxyacetic acid titanate.

7. A method for preparing a low linear expansion coefficient polyphenylene sulfide composite material as described in any one of claims 1 to 6, comprising the following steps: S1. Weigh out the polyphenylene sulfide resin, low-expansion filler system, coupling agent, lubricant and colorant by weight. S2. Add the polyphenylene sulfide resin and coupling agent to a high-speed mixer and mix them to pre-disperse the coupling agent on the surface of the PPS resin. S3. Add lubricant and colorant to the mixture obtained in step S2 and continue mixing; when the formula contains nano-sized fillers, add the nano-sized fillers together with the lubricant and colorant and mix. S4. Add the mixture obtained in step S3 into a twin-screw extruder, while separately feeding the sheet-like filler and / or fibrous filler. After melt blending, extrusion, cooling, and pelletizing, a polyphenylene sulfide composite material with a low linear expansion coefficient is obtained.

8. The preparation method according to claim 7, characterized in that, In S2, the mixing time is 2 minutes, and in S3, the mixing time continues for 2 minutes.

9. The preparation method according to claim 7, characterized in that, In S4, the temperatures of each zone of the twin-screw extruder from the feed inlet to the die head are set sequentially as follows: 250℃, 250℃, 325℃, 325℃, 325℃, 325℃, 315℃, 315℃, 315℃, 315℃, 330℃.

10. The application of a low linear expansion coefficient polyphenylene sulfide composite material as described in any one of claims 1 to 6 in precision instruments, electronic packaging, electronic and electrical components, automotive components, or aerospace components.